DETERMINATION OF STRESS RESPONSES INDUCED BY ALUMINUM IN MAIZE (ZEA MAYS) - (:unkn) unknown (AKADEMIAI KIADO ZRT, 2011)
To assess the alternative responses to aluminum toxicity, maize (Zea mays L. cv Karadeniz yildizi) roots were exposed to different concentrations of AlCl3 (150, 300 and 450 mu M). Aluminum reduced the root elongation by 39.6% in 150 mu M, 44.1% in 300 mu M, 50.1% in 450 mu M AlCl3 after 96 h period. To correlate the root elongation with the alternative stress responses including aluminum accumulation, lipid peroxidation, mitotic abnormalities, reduction of starch content, intracellular Ca2+ accumulation, callose formation, lignin deposition and peroxidase activity, cytochemical and biochemical tests were performed. The results indicated that aluminum accumulation and lipid peroxidation were observed more densely on the root cap and the outer cortex cells. In addition to morphological deformations, cytochemical analysis displayed cellular deformations. Furthermore, mitotic abnormalities were observed such as c-mitosis, micronuclei, bi- and trinucleated cells in aluminum treated root tips. Aluminum treatment induced starch reduction, callose formation, lignin accumulation and intracellular Ca2+ increase. Moreover, the peroxidase activity increased significantly by 3, 4.4 and 7.7 times higher than in that of control after 96 h, respectively. In conclusion, aluminum is significantly stressful in maize culminating in morphological and cellular alterations.
Keywords: Aluminum toxicity; root growth; callose; intracellular Ca2+; peroxidase activity; ROOT-GROWTH; LIPID-PEROXIDATION; CELL-DEATH; TOXICITY; INHIBITION; TOLERANCE; BARLEY; EXPRESSION; MECHANISM; DYNAMICS